Risk factors for mortality in pseudomonas aeruginosa bacteremia in children - Jian Chen; Haixin Huang; Chengjun Liu; Yue-qiang Fu (Pediatrics and Neonatology)
Background: The incidence of Pseudomonas aeruginosa (P. aeruginosa) bacteremia in children ranks third to fourth among gram-negative bacilli bacteremia, which is one of the main conditional pathogens in hospitals. This study aimed to identify the clinical characteristics and risk factors of 60-day in-hospital mortality in children with P. aeruginosa bacteremia. Methods: This retrospective study was conducted in a tertiary pediatric hospital between January 2015 and December 2021 including children with P. aeruginosa bacteremia. Kaplan–Meier survival analysis was used to investigate the time-to-event outcomes. Logistic regression was used to explore the independent risk factors for 60-day mortality. Results: Overall, 75 patients with P. aeruginosa bacteremia episodes were identified. Immunosuppression (52%) was the most common underlying condition, followed by neutropenia (50.7%) and hematological malignancies (48%). Among 75 patients with P. aeruginosa bacteremia, 25 (33.3%) had septic shock, 30 (40%) had respiratory failure, and 20 (26.7%) had liver function impairment. The 60-day in-hospital mortality was 17.3%. In multivariate analysis, independent risk factors for 60-day mortality were respiratory failure [odds ratio (OR) 39.329; 95% CI:3.212–481.48, P = 0.004) and liver function impairment (OR 17.925; 95% CI:2.909–139.178, P = 0.002). Conclusion: Respiratory failure and liver function impairment seem to be related to poor prognosis in children with P. aeruginosa bacteremia.